THE MODEL OF AVALANCHE — RELATING EFFECT IN THE PROCESS OF IMAGES RECONSTRUCTION IN THE COMBINED CRYPTOSEMANTIC SYSTEMS ON THE BASE OF POLYADYC PRESENTATION - Barannik, V.; Sydchenko, S.; Larin, V. (Science-based technologies, 2010)
The basic stages of methodology hiding construction of semantic structure of images are expounded in decoded proof systems on the base of 2-D polyadic presentation as a result of decoding on the by mistake neat grounds of DPN elements, being based on: forming of the official information system on the base of dynamic ranges of DPN elements; models of avalanche relating effect in the process of images reconstruction in combined crypto semantic systems on a base poliadic presentations.